Mitigating Geometric Bottlenecks in One-Way Systems: Empirical Evaluation and Intervention Models in Critical Urban Arteries - Alfath Yogatama; Abdullah Ade Suryobuwono; Ervin Widodo; Aang Gunawan; Zaenal Abidin (Jurnal Ilmu Multidisiplin, 2026)
Urban congestion represents a critical challenge in metropolitan transportation systems, particularly in one-way traffic corridors experiencing geometric bottlenecks. This study evaluates the implementation of one-way systems on Jalan Gading Indah Raya and proposes evidence-based intervention models to enhance traffic performance at Pintu Satu Gading, North Jakarta. Employing mixed-method triangulation, the research integrates field surveys, Indonesian Road Capacity Manual (PKJI) analysis, and PTV Vissim microsimulation modeling to assess existing conditions and evaluate intervention scenarios. Field data revealed peak traffic volumes reaching 6,804 vehicles per hour with speeds declining to 16 km/h, indicating severe saturation conditions. Three intervention scenarios were simulated, incorporating geometric modifications, signal timing optimization, and traffic management strategies. Results demonstrate that integrated interventions can improve degree of saturation by 23-31%, enhance average speeds by 18-27%, and elevate the level of service from D/E to B/C categories. The study validates microsimulation as an effective tool for evaluating traffic interventions in complex urban networks and provides actionable recommendations for transportation authorities managing geometric bottlenecks in one-way arterial systems.